2020
DOI: 10.1007/jhep10(2020)124
|View full text |Cite
|
Sign up to set email alerts
|

One-loop non-planar anomalous dimensions in super Yang-Mills theory

Abstract: We consider non-planar one-loop anomalous dimensions in maximally supersymmetric Yang-Mills theory and its marginally deformed analogues. Using the basis of Bethe states, we compute matrix elements of the dilatation operator and find compact expressions in terms of off-shell scalar products and hexagon-like functions. We then use non-degenerate quantum-mechanical perturbation theory to compute the leading 1/N2 corrections to operator dimensions and as an example compute the large R-charge limit for two-excitat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 77 publications
(129 reference statements)
0
10
0
Order By: Relevance
“…See also recent interesting work on non-planar anomalous dimensions[24] 2. The full solution to the spectral problem was obtained by Quantum Spectral Curve[38,39] 3.…”
mentioning
confidence: 99%
“…See also recent interesting work on non-planar anomalous dimensions[24] 2. The full solution to the spectral problem was obtained by Quantum Spectral Curve[38,39] 3.…”
mentioning
confidence: 99%
“…Now by working with eigenvectors of P, which is also necessary to fully desymmetrise the spectrum, we can choose a basis of states such that P = +1 and the Hamiltonian is real and symmetric when restricted to these sectors. This construction can be generalised to a time-reversal symmetry of the one-loop non-planar dilatation operator of N = 4 SYM theory by interpreting P as the operator which reverses the order of fields within individual traces of gauge-invariant operators and so explains the GOE statistics seen in [48,49].…”
Section: Level-spacing Statisticsmentioning
confidence: 99%
“…In particular, the BGS conjecture [47] states that quantum-chaotic systems have spectra whose fluctuations are described by Random Matrix Theory (RMT). An analysis of the spectrum of the planar dilatation operator of N = 4 SU(N ) SYM theory expanded in the 't Hooft coupling λ was performed in [48] and [49], and it was shown that, for rank-one sectors of the one-loop planar theory, the spacing between adjacent levels is described by the Poisson distribution as is characteristic of integrable systems [50]. However, when non-planar corrections are included, the spectrum becomes chaotic and the level spacings closely follow the Wigner-Dyson distribution for the Gaussian Orthogonal Ensemble (GOE).…”
Section: Introductionmentioning
confidence: 99%
“…The Bethe states from algebraic Bethe ansatz and the ones from coordinate Bethe ansatz are related by |u, v, w al ∝ i<j u i − u j + i u i − u j i<j v i − v j + i v i − v j i<j w i − w j + i w i − w j |u, v, w co , (D. 24) with a proportional factor which is invariant under the permutations of rapidities of the same type.…”
Section: Nested Algebraic Bethe Ansatzmentioning
confidence: 99%
“…See also recent interesting work on non-planar anomalous dimensions[24] 2. We should however note that the (non-)integrability of the sub-determinant operators is not fully settled even for N = 4 SYM.…”
mentioning
confidence: 98%